Use pattern of social networks among undergraduate students and its implications on library use and usefulness in higher learning institutions - Malekani, Andrew W. (Access: An International Journal of Nepal Library Association, 2023)
This study used a mixed method approach design which included quantitative and qualitative study to explore use pattern of social by undergraduate students SUA. The target population of this study was 3000 undergraduate students in their first, secondhand third year at SUA stationed at Solomon Mahlangu Campus (SMC) available during the year 2021. Stratified random sampling was used to get three strata: first, second and third year undergraduates. From each stratum, 30 students were selected systematically by picking their names from the student registers of classes available from admissions office. Thus, a total of 90 students were given a questionnaire to fill in. The results have indicated that, undergraduate students are using social networks in their everyday life and it is having a positive impact on them by providing them with reliable information on the day-to-day activities. The common social networks have been found to be Whats App, Facebook, Google docs. None of the respondents were found to be using LinkedIn; asocial network very important especially for the students since it helps them in creating good connections and an easier job seeking option once the schooling days are done. The students have reported their preference of social networks over the traditional library, something that results in declining trend in the use of traditional library in the institutions. It can therefore be concluded that social media have become inevitable technologies that help students in accessing information, let alone other services like entertainment and so on. The students have an understanding on social networks but there is a need for libraries to utilize these networks to promote information access. Social Network Entrepreneurship skills should also be taught to students so as to put into good use the social networks students are already using beneficially. When students are encouraged to use social media available or linked to library websites, the use of traditional library will continue as it used to be in the past.